2014
DOI: 10.1039/c4nj00794h
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic properties of Bi/BiOCl heterojunctions synthesized using an in situ reduction method

Abstract: Bi nanoparticles are grown on BiOCl nanosheets via an in situ chemical reduction in a KBH 4 aqueous solution.Bi/BiOCl nanosheets with different contents of Bi nanoparticles can be achieved by changing the concentration of the KBH 4 solution. The structure, morphology, elemental composition and optical absorption performance are characterized using an X-ray diffraction diffractometer, a scanning electron microscope, a high resolution transmission electron microscope, an X-ray photoelectron spectrometer and a UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…This method makes the combination of Bi and BiOCl 0.5 I 0.5 much better than those prepared by common deposition because of the lattice matching in the interface is better, which is benefi cial to the photocatalytic activity. [19][20][21] After reduction, the color of the BiOCl 0.5 I 0.5 fi lm fi rst changed from pale yellow to black (inset in Figure S3, Supporting Information), likewise the morphology changed obviously. Roughened surface of the reductive BiOX nanosheets can be obviously observed in Figure S3 Figure S4 (Supporting Information), the overall XPS spectra exhibited no noticeable difference between as-prepared BiOX nanosheets and the reductive BiOX nanosheets.…”
Section: Preparation and Characterization Of Biox Nanosheetsmentioning
confidence: 96%
See 1 more Smart Citation
“…This method makes the combination of Bi and BiOCl 0.5 I 0.5 much better than those prepared by common deposition because of the lattice matching in the interface is better, which is benefi cial to the photocatalytic activity. [19][20][21] After reduction, the color of the BiOCl 0.5 I 0.5 fi lm fi rst changed from pale yellow to black (inset in Figure S3, Supporting Information), likewise the morphology changed obviously. Roughened surface of the reductive BiOX nanosheets can be obviously observed in Figure S3 Figure S4 (Supporting Information), the overall XPS spectra exhibited no noticeable difference between as-prepared BiOX nanosheets and the reductive BiOX nanosheets.…”
Section: Preparation and Characterization Of Biox Nanosheetsmentioning
confidence: 96%
“…The synthesis and modifi cation of Bi-based semiconductor photocatalysts has attracted intense research interest. Recently, several photo catalysts with Bi element deposited have been reported, such as Bi/BiOCl, [ 19,20 ] Bi/Bi 2 O 3 , [ 21 ] and Bi/BiOI. [ 22 ] These nanocomposite photocatalysts show superior photocatalytic performance in comparison with their separate components due to the existence of Bi metal, where it may enhance light absorption, charge separation effi ciency, and the charge transfer rate.…”
mentioning
confidence: 99%
“…Compared to noble metals, Bi is more cheaper; moreover, Bi is one component of BiOCl, which is beneficial for the in situ reduction and one pot synthesis of Bi nanoparticle modified BiOCl with better lattice matching in the interface [28]. Recently, some researchers found that metallic Bi modification could enhance the photocatalytic efficiency of BiOCl photocatalysts [29,30].…”
Section: Introductionmentioning
confidence: 98%
“…can serve as electron traps and improve the separation of electron-hole pairs. Bismuth (Bi) is a semimetal with a very small band gap, possessing a highly anisotropic Fermi surface, low carrier density, small carrier effective mass, and a long carrier mean free path [28].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the self-doped BiOI 1.5 exhibited very high photocatalytic activity in methyl orange degradation [23]. Some other bismuth-based photocatalysts include: Bi [24], BiOBr [25], BiOi/BiOCl [26], Bi 24 O 31 Br [27], Bi 4 NbO 8 Br [28], black BiOCl [29], Bi/ BiOCl [30], BiFeO 3 [31], Bi 4 Ti 3 O 12 [32], Bi 2 MoO 6 [33], Bi 2 O 2 CO 3 [34,35] and Bi 2 O 3 [36].…”
Section: Introductionmentioning
confidence: 99%